Analisis Pajak Daerah Dan Retribusi Daerah Terhadap Pertumbuhan Ekonomi Melalui Pendapatan Asli Daerah Di Kabupaten Mojokerto - Yasintus Solendro; Soter Epistomio Ot Suna; Aloisius Hama (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This purpose of this research to examine the effect of regional taxes and regional levies on economic growth, using local original income as an intervention variable in Mojokerto Regency in 2018-2023. This type of research is quantitative. The data used is secondary data with data collection techniques using documentation techniques. The sample selection method in this study used a saturated sampling method. The data analysis technique used in this research is SmartPLS 3.0. The results of this research are that regional taxes and regional levies have no effect on economic growth. Regional taxes and regional levies influence regional original income. Regional original income influences economic growth. Original regional income cannot mediate the effect of regional taxes and regional levies on economic growth.